2005
DOI: 10.1007/s00248-004-0171-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Colonization of the Phyllosphere of Mediterranean Perennial Species as Influenced by Leaf Structural and Chemical Features

Abstract: In this study, we assessed various leaf structural and chemical features as possible predictors of the size of the phyllosphere bacterial population in the Mediterranean environment. We examined eight perennial species, naturally occurring and coexisting in the same area, in Halkidiki (northern Greece). They are Arbutus unedo, Quercus coccifera, Pistacia lentiscus, and Myrtus communis (evergreen sclerophyllous species), Lavandula stoechas and Cistus incanus (drought semi-deciduous species), and Calamintha nepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 69 publications
4
102
0
Order By: Relevance
“…Levels of bacterial epiphytic phyllosphere colonization have been reported to range from 10 1 to 10 8 CFU g Ϫ1 between different plant genera (18,20,53). Total bacterial colonization of the lettuce phyllosphere in this study ranged from 4 ϫ 10 5 to 5 ϫ 10 6 CFU g (FW) Ϫ1 , which is comparable to the levels of epiphytic lettuce colonization (18).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Levels of bacterial epiphytic phyllosphere colonization have been reported to range from 10 1 to 10 8 CFU g Ϫ1 between different plant genera (18,20,53). Total bacterial colonization of the lettuce phyllosphere in this study ranged from 4 ϫ 10 5 to 5 ϫ 10 6 CFU g (FW) Ϫ1 , which is comparable to the levels of epiphytic lettuce colonization (18).…”
Section: Discussionsupporting
confidence: 69%
“…The microbial population already resident in the phyllosphere is also likely to impact significantly on the ability of incoming organisms to successfully colonize the leaf surface. Variation in such resident populations between different plant species has been attributed to differences in a range of plant physiochemical characteristics, including the water and phosphorus contents of the leaves, levels of phenolic compounds (which may be inhibitory toward many bacteria), and leaf and mesophyll thickness (53). All of these plant characteristics have a genetic basis.…”
mentioning
confidence: 99%
“…Leaf age and leaf surfaces also influence the abundance of phyllosphere bacterial populations [15]. Concomitant with this, it was reported that bacterial abundance on the phyllosphere were negatively correlated with the concentration of phenolic substances, thickness of total leaf, mesophyll thickness and thickness of leaf cuticle [42].…”
Section: Discussionmentioning
confidence: 83%
“…The epiphyte population is dominated by bacteria which can be found in numbers ranging from 10 5 to 10 7 cells/g of plant material (Yadav et al, 2005). Artur et al, (2015) (Table 2).…”
Section: Bacterial Count In Phyllosphere Of Potato Plantmentioning
confidence: 99%